Discovering implicit associations in a case of encapsulating peritoneal sclerosis complicated by severe mineral imbalance. (3rd November 2014) - Pinho, Ana; Pinto, Isabel; Sampaio, Sandra; Neves, Pedro
Abstract : We describe the case of a 42-year-old woman who developed encapsulating peritoneal sclerosis (EPS) after 7 years on peritoneal dialysis, with clinical relief by enterolysis associated to treatment with tamoxifen, corticosteroids and parenteral nutrition in haemodialysis. During the next 7 months, she was also conservatively stabilised for mild hyperparathyroidism until she was admitted with calciphylaxis, associated with massive extraosseous calcification. Despite parathyroidectomy and sodium thiosulfate treatment, which resulted in a successful resolution of calciphylaxis, she died 1 year later due to a gross calcified peritoneum. In view of controlled hyperparathyroidism, the massive extraosseous calcification beginning after EPS diagnosis furthermore corroborates a recently suggested role for calcium-regulatory factors associated with poor outcome in EPS.